Protective role of melatonin in mouse spermatogenesis induced by sodium arsenite - Bustos-Obregon, Eduardo; Poblete, Daniel; Catriao, Roberto; Fernandes, Fabio Henrique [UNESP] (Soc Chilena Anatomia, 2013)
Arsenic is a testicular environmental toxic. Melatonin (Me), being a potent antioxidant, may reduce the damage caused by arsenic in male fertility. The effects of daily oral exposure of Sodium Arsenite (As; 7.0 mg/kg/bw); Melatonin (Me, 10.0 mg/kg/bw); Me (10.0 mg/kg/bw) plus As (7.0 mg/kg/bw), and Negative Control (NaCl 0.9%) in male CF-1 adult mice were assessed in acute (8.3 days), chronic (33.2 days) and recovery (66,4 days) of testicular damage. We evaluated changes in testicular weight and histopathological, morphometric measurements, expression of COX-2 and Androgen Receptor (AR) antigens and lipid peroxidation levels. Treatment resulted in decreased tubular diameter and AR expression, and increased: interstitial area, luminal diameter, COX-2 expression levels and of lipid peroxidation. Co-administration of As and Me partially decreased germ cell degeneration and AR expression levels, improving testicular histopathological parameters. These results indicate that As causes toxicity and testicular germ cell degeneration by induction of oxidative stress. Me partially protects from this damage in mouse testis, acting as scavenger of oxygen radical species.
Keywords: Mouse; Arsenic; COX-2; Androgen receptor; Oxidative stress; Melatonin